There is More (to) Life than COVID-19 - Oliveira, Jaime; Cerqueira, Ana Rita; Silva Monteiro, Joana; Marques, Maria Manuel (Gazeta Médica, 2022)
COVID-19 has become the main diagnostic hypothesis in many consultations. This case highlights the need to maintain the holistic approach, characteristic of General Practice/Family Medicine. A 43-year-old woman, with history of adjustment disorder, fibromyalgia and uterine fibroids, usually medicated with: duloxetine; lorazepam; desogestrel. She was evaluated in “ADR-Comunidade” for headache, nausea, dysgeusia, odynophagia, cough, dyspnea, myalgias and asthenia, without fever. She was prescribed test for COVID-19 and recommended isolation. She was contacted within the scope of “Trace COVID-19®”, noting forgetfulness in taking contraceptive and amenorrhea. A pregnancy was considered, which the patient denied. The test for COVID-19 was negative, however, there was a symptomatic worsening that justified referral to emergency department, where an 11-week pregnancy was diagnosed. COVID-19 mimics several clinical situations. The devaluation of amenorrhea and a directed approach in “ADR” led to diagnostic delay, making voluntary termination of pregnancy impossible although the unwanted pregnancy.